O consumo das famílias brasileiras: Um olhar de gênero e raça - Luana Passos; Ana Luiza Neves de Holanda Barbosa; Danielle Carusi Machado; Luciana Alves dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The objective of this study is to analyze the patterns of Brazilian household consumption based on the gender and race of the head of the household. To do so, we estimated a simultaneous demand system for the six main aggregate consumption categories: housing, transportation, food, health, education, and other expenses. The analysis was done with the 2017-2018 Household Budget Survey, by National Statistical Bureau. Our results suggest that women spend more on housing than men, while men invest more resources in transportation expenses than women. As for consumption patterns by race, the results suggest that in food expenses, black households spend more than white, regardless of the gender of the household head. In health and education expenses, white household heads spend more than black, and, about health, white women tend to spend more than men. Income, education, age, and children are important factors that may explain differences in these results.
Keywords: D12; J15; J16; 330; household consumption; gender; race; Consumer Expenditure Survey